RATIO LEGIS OF SETTING TIME LIMITS FOR JUDGES IN RETURNING DISPUTES IN INDUSTRIAL RELATIONS UNDER ARTICLE 103 LAW NUMBER 2 OF 2004 - Yowana I M.A.; Fadli M.; Permadi I.; Santoso B. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
This article is results from legal research on setting time limits for judges to decide industrial relations disputes with legal certainty and justice. This study aims to examine and analyze the ratio legis Article 103 of Law Number 2 of 2004. This research is normative legal research using a statutory approach. This study's conclusion shows that the ratio legis for setting time limits for judges in deciding industrial relations disputes under Article 103 of Law Number 2 of 2004 can be examined into three aspects: philosophical, sociological, and juridical. The philosophical aspects consist of ontology, epistemology, and axiology. Ontology, employers are considered to have a stronger bargaining position than workers. Epistemologically, the settlement of industrial relations disputes is carried out in two ways: non-litigation (bipartite and tripartite) and litigation. Axiologically, the settlement of industrial relations disputes is known as quick value. Sociological Aspects, as a form of social protection and economical protection for workers. The juridical aspect, provides legal protection for workers from formal aspects.